Analysis of Pedagogical Content of Biology Text Books on Structures and Functions of Animal Tissues for Class XI - Rahma Wati; Edy Chandra; Asep Mulyani (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Textbooks will not be separated from the applied curriculum. There are four aspects analyzed in the pedagogical content analysis of the textbook research: the accuracy of concepts, the accuracy of curriculum objectives, the readability of texts, and the visual representation. This study aimed to compare the pedagogical content of biology textbooks on structures and functions of animal tissues from different curricula (the 2006 Education Unit Level Curriculum, the 2013 Curriculum, and the 2016 Revised Edition of the 2013 Curriculum) for class XI. This research employed a descriptive qualitative method and a content analysis technique. The research sample was the biology textbooks for class XI compiled by Sri Pujiyanto and published by Platinum. The research instrument was a content analysis protocol by codification (data coding). The results showed that the accuracy aspects in the sample books with the 2006 Education Unit Level Curriculum, the 2013 Curriculum, and the 2016 Revised Edition of the 2013 Curriculum were more dominant and categorized as adequate. The books with the 2013 Curriculum and the 2016 Revised Edition had better accuracy than those with the 2006 Education Unit Level Curriculum book. The text readability aspect of the three sample books was not suitable for class XI students. The books with the 2013 Curriculum and the 2016 Revised Edition of 2013 Curriculum had better visual representation than the book with the Education Unit Level Curriculum. The three sample books showed that the relationship with the material content was more dominant in the meaningful category, the relationship with reality was more dominant in the real category, and the visual representation function was more dominant in the explanatory category.